Optimization of the thermochromic glazing design for curtain wall buildings based on experimental measurements and dynamic simulation. (1st March 2021) - Arnesano, Marco; Pandarese, Giuseppe; Martarelli, Milena; Naspi, Federica; Gurunatha, Kargal L.; Sol, Christian; Portnoi, Mark; Ramirez, Francisco V.; Parkin, Ivan P.; Papakonstantinou, Ioannis; Revel, Gian Marco
Highlights: Thermochromic glazing properties have been measured under variable temperature conditions with customized spectrophotometer. Procedure for thermochromic thin film preparation has been presented. Building energy simulation has been implemented for impact assessment. Optimization of the thermochromic properties has been performed for different climates. A complete procedure for thermochromic design and optimization has been described. Abstract: Thermochromic (TC) glazing could provide a significant reduction of energy consumption in curtain wall buildings. However, each application requires a design tailored to building's specifications. This paper proposes a complete approach for designing TC glaze based on building energy simulation starting from the production of thin thermochromic layers and the measurements of their optical properties by means of a customized spectrophotometer. The main focus of this work is to identify the optimal TC optical response that minimises the building energy consumption. Energy simulations have been performed for a virtual mock-up set at two locations with different climates, Italy and Poland. A set of profiles, each one determining thermochromic properties in terms of switching temperature, range of solar transmittance and transition speed, have been created with a fine step of temperature (2 °C) and used to simulate different scenarios. The outcome of the optimization provided the optimal properties to achieve the right balance between cooling energy reduction and heating energy increase due to the application of the thermochromic layer, in comparison to a standard clear glass. The fine step in switching temperature allowed to accurately estimate the subtle differences for the two different climates (25 °C Italy, 24–26 °C Poland). The highest impact has been found for the Italian location with a maximum reduction of total energy consumption of 22.8%. This was achieved with a thermochromic switching at 25 °C, with fast transition and range of transmittance between 0.1 (switched state) and 0.5 (normal state), which is a not extreme behaviour.